2018
DOI: 10.1016/j.chemosphere.2018.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Emerging contaminants in Brazilian rivers: Occurrence and effects on gene expression in zebrafish (Danio rerio) embryos

Abstract: Emerging contaminants (ECs) are synthetic or naturally occurring chemicals that are not commonly monitored despite having the potential of entering the environment and causing adverse ecological and/or human health effects. This study aimed to determine whether ECs are present in the surface waters of two rivers in Mato Grosso do Sul State, Brazil, and evaluate the effects of ECs mixtures at environmentally relevant concentrations on zebrafish (Danio rerio) gene expression. ECs concentrations were determined u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(30 citation statements)
references
References 62 publications
1
21
0
8
Order By: Relevance
“…The presence of atrazine, carbendazim, imidacloprid, hexazinone and tebuthiuron in the Mato Grosso do Sul State was also evaluated by the researchers, with concentrations lower than 0.1 µg L -1 . 15 Effective concentrations (EC, 50%) of diuron were reported in the literature at the same range of those found in SP 5, 7 and 9 (1.03-12.59 µg L -1 ). 42 Researchers also have been studying imazethapyr and tebuconazole concentrations in surface water surrounded by rice crop areas, where the maximum concentrations reported for these compounds were 0.326 and 0.015 µg L -1 , .…”
Section: Pesticides Quantification In Samplessupporting
confidence: 53%
See 2 more Smart Citations
“…The presence of atrazine, carbendazim, imidacloprid, hexazinone and tebuthiuron in the Mato Grosso do Sul State was also evaluated by the researchers, with concentrations lower than 0.1 µg L -1 . 15 Effective concentrations (EC, 50%) of diuron were reported in the literature at the same range of those found in SP 5, 7 and 9 (1.03-12.59 µg L -1 ). 42 Researchers also have been studying imazethapyr and tebuconazole concentrations in surface water surrounded by rice crop areas, where the maximum concentrations reported for these compounds were 0.326 and 0.015 µg L -1 , .…”
Section: Pesticides Quantification In Samplessupporting
confidence: 53%
“…9,41 A study performed with samples collected from two rivers from Mato Grosso do Sul State, an area with a strong agricultural activity obtained concentrations of diuron lower than 0.01 µg L -1 . 15 The lowest concentration of diuron in the present work was 0.16 µg L -1 . The presence of atrazine, carbendazim, imidacloprid, hexazinone and tebuthiuron in the Mato Grosso do Sul State was also evaluated by the researchers, with concentrations lower than 0.1 µg L -1 .…”
Section: Pesticides Quantification In Samplesmentioning
confidence: 46%
See 1 more Smart Citation
“…In a study of 16 Brazilian rivers, cocaine was found above the quantification limit in 85% of the samples studied with concentrations between 6 to 62 ngL -1 ; its metabolite, benzoylecgonine, was also found in 94% of the samples and with concentrations between 10 and 1019 ngL -1 (Campestrini and Jardim, 2017). A study of the surface waters of the Dourados and Brilhante Rivers in the state of Mato Grosso do Sul, Brazil, found 9 of the 21 ECs studied, with caffeine the most-concentrated (Maximum: 1040 μgL -1 ) (Sposito et al, 2018). In another study done in Brazil, 8 ECs were found in the Ave River and 13 in the Sousa River among the 17 ECs studied (Sousa et al, 2019).…”
Section: Occurrence Of Emerging Contaminants In Surface Watersmentioning
confidence: 89%
“…Sposito et al (2018) detected caffeine in all analyzed samples of the Dourados and Brilhante rivers 31 . The highest concentration of caffeine determined was 1040 ng L -1 , measured at a point near the city of Dourados, a city with 218,000 inhabitants.…”
Section: Caffeine As An Emerging Contaminant: Concentrations and Ecotmentioning
confidence: 99%